CEO overpower and corporate social responsibility of commercial banks: The moderating role of state ownership - Khoa Dang Duong; Phuong Mai Duong Tran; Pham Ha (Cogent Economics & Finance, 2023)
This study examines the impacts of powerful CEOs and state ownership on commercial banks' corporate social responsibility (CSR) in Vietnam, a transitional market in Asia. Given the differences between emerging and developed markets in terms of their institutions and governance, it is essential to explore the impact of CEO power on CSR disclosure in emerging markets. This study collects data from 37 Vietnamese commercial banks from 2010 to 2020. We employ a dynamic system Generalized Method of Moments to overcome endogeneity and heterogeneity issues. The findings show that powerful CEOs negatively reduce CSR programs. CEO power tends to focus less on CSR investments because CSR expenses reduce the operating free cash flow. Meanwhile, our findings indicate a positive relationship between state ownership and CSR developments. This study reports a moderating role of state ownership in empowering powerful CEOs to develop CSR programs in commercial banks. We also perform a robustness test to confirm the persistence of our main findings across subsamples by CEO ages. Our robustness test results indicate that CEOs have the lowest motivation to improve CSR when their ages are from 40 to 60. Our findings align with agency theory, stakeholder theory and prior literature. Finally, our study contributes practical implications for management and policymakers to develop CSR programs sustainably.
Keywords: G20; G21; 330; CEO overpower; commercial banks; Corporate social responsibility; GMM; state ownership; Vietnam